INTERRELIGIOUS DIALOG PRINCIPLES IN DIGITAL MEDIA: THE CASE OF MOHAMMADIA LEAGUE OF SCHOLARS IN MOROCCO - Abdelhak, Karim; Rhoulami, Khadija (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
The League of Mohammadia Scholars as a religious institution in Morocco plays a role in promoting the principles of peace and religious tolerance through the lens of digital media. Through quantitative methods with the theoretical frameworks of media, institutional communication, and interfaith dialog, we attempted to look at culture as it relates to peace and tolerance. Through the responses collected, we identified key patterns, trends, and insights that provided a deeper understanding of the subject under study. Fundamental to this is the need to use modern media such as social media and new media to expand the scope and impact of interfaith dialogue to realize a moderate and tolerant Islam.